Descriptive Practices for Electronic Records: Deciding What Is Essential and Imagining What Is Possible - Hedstrom, Margaret (Archivaria, 1993)
The challenges raised by electronic records present an opportunity to define the essential purposes for description: to reassess its objectives, agents, and timing; and to imagine new approaches that harness the power of information technology while respecting archival principles. This article discusses how archival description must support the need to identify, gain access, understand the meaning, interpret the content, determine authenticity, and manage electronic records to ensure continuing access. Management of metadata is proposed as an alternative strategy to current descriptive practices. RÉSUMÉ Les défis soulevés par les archives électroniques présentent une occasion de définir les buts essentiels de la description, c’est-à-dire réévaluer ses objectifs, ses représentants et sa fréquence, et d’imaginer de nouvelles approches qui, bien qu’étroitement rattachées au pouvoir de la technologie de l’information, n’en respectent pas moins les principes de l’archivistique. Cet article examine comment la description archivistique doit soutenir le besoin d’identifier, d’avoir accès, de comprendre la signification, d’interpréter le contenu, déterminer l’authenticité et gérer les archives électroniques afin d’en assurer l’accès de manière permanente. La gestion de la méta-information est proposée comme une stratégie alternative aux pratiques descriptives actuelles.